QUALITY DETERMINATION OF ROHU (Labeo rohita) DURING ICE STORAGE - K. Dhanapal; K. Sravani; A. Balasubramanian; G.V.S. Reddy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An investigation on quality assessment of rohu (Labeo rohita) stored in ice was carried out through sensory, microbial and chemical analyses. Significant changes in the proximate composition of ice stored fish in different days were observed (P < 0.01) except for minerals (P >0.01). The organoleptic quality of the ice stored fish was significantly (P < 0.01) influenced by the Total Volatile Base Nitrogen (TVBN), Trimethylamine Nitrogen (TMAN) Thio Barbutric acid (TBA), Free Fatty Acids (FFA) and Water Holding Capacity (WHC) and microbial counts. Total Plate Count (TPC) of mesophilic bacteria and Staphylococcus aureus decreased continuously while Psychrophiles, Pseudomonas and Aeromonas spp. increased in count. Escherichia coli, Faecal streptococci , Vibrio spp., Salmonella spp. and Listeria monocytogenes were completely absent throughout the study. Organoleptic quality tests showed that the maximum shelf life of rohu in ice was 17 days.